2017
DOI: 10.3389/fimmu.2017.01856
|View full text |Cite
|
Sign up to set email alerts
|

Allicin Alleviates Reticuloendotheliosis Virus-Induced Immunosuppression via ERK/Mitogen-Activated Protein Kinase Pathway in Specific Pathogen-Free Chickens

Abstract: Reticuloendotheliosis virus (REV), a gammaretrovirus in the Retroviridae family, causes an immunosuppressive, oncogenic, and runting–stunting syndrome in multiple avian hosts. Allicin, the main effective component of garlic, has a broad spectrum of pharmacological properties. The hypothesis that allicin could relieve REV-induced immune dysfunction was investigated in vivo and in vitro in the present study. The results showed that dietary allicin supplementation ameliorated REV-induced dysplasia and immune dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 42 publications
1
46
1
1
Order By: Relevance
“…2 ) ( Weber et al, 1992 ). It is well stablished that OSCs, and allicin and its derivatives contribute significantly to garlics antiviral properties ( Bayan et al, 2014 ; Sharma, 2019 ; Wang et al, 2017 ). The OSCs are highly reactive to the thiol group present in various active viral proteins or enzymes that are crucial for microbial surveillance and fusion ( Ankri & Mirelman, 1999 ; Jain et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 ) ( Weber et al, 1992 ). It is well stablished that OSCs, and allicin and its derivatives contribute significantly to garlics antiviral properties ( Bayan et al, 2014 ; Sharma, 2019 ; Wang et al, 2017 ). The OSCs are highly reactive to the thiol group present in various active viral proteins or enzymes that are crucial for microbial surveillance and fusion ( Ankri & Mirelman, 1999 ; Jain et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which garlicin inhibits the replication of HIV-1 is not clear but it has been proposed that garlicin, being a thiol compound, inhibits phorbol ester stimulated HIV-1 replication or inhibits ‘HIV-1 tat’, a transactivator protein of HIV-1 replication, similar to other thiol compounds (N-acetyl- l -cysteine and 2,3-dimercapto-1-propanol) ( Kubota et al, 1990 ; Roederer et al, 1990 ; Shoji et al, 1993 ). There was no report found on allicin ability to inhibit HIV, but a recent study reported that allicin can inhibit replication of reticuloendotheliosis virus (REV) and alleviates the infection in chicken ( Wang et al, 2017 ). REV is a retrovirus in the Retroviridae family and causes an immunosuppressive syndrome in different avian hosts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High mortality was one of the important limiting factors during fish larvae culture, and more attention has been paid to enhance larval health to improve the survival rate ( Rojo-Cebreros et al, 2018 ). Allicin has been used as immunostimulants to enhance the immune response in mice ( Bruck et al, 2005 ), chicken ( Wang et al, 2017 ), pig ( Lan et al, 2017 ) and many fish species ( Nya and Austin, 2011 ; Abdel-Daim et al, 2015 ; Xu et al, 2020 ). NO is a key molecule in the immune-neuroendocrine integration cooperating with other molecules in vertebrates ( Pederzoli and Mola, 2016 ), and showed protective roles of immuno-protection against pathogenic infection via regulating Akt and ERK pathway ( Zhou et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%